Home and the World - Rabindranath Tagore (Rupa Publications, 2002)
The Home and the World is the translation of Ghare-Baire, one of Tagore\'s major novels. It was serialized in Sabujpatra in 1915-16. It is a love triangle with Bimala the wife, Sandip the lover and Nikhilesh the husband. The prose is replete with barbed irony and needle-sharp epigrams.